The Influence of Intellectual Capital, Green Accounting, And Company Size on Financial Performance In Mining Companies Listed on The Indonesian Stock Exchange Period 2020-2024 - Ronny Andesto (Jurnal Ilmiah Manajemen dan Bisnis, 2026)
This study aims to see and analyze the impact produced by intellectual capital, green accounting, and company size on financial performance. The population in this study are all mining companies listed on the Indonesia Stock Exchange for the period 2020-2024. The sampling technique in this study is the perposive sampling technique by determining several sampling criteria,. The data analysis technique used in this study is to use Multiple Linear Regression with the help of SPSS Version 27. The results in this study indicate that intellectual capital, has an effect on financial performance; green accounting, and company size have no effect on financial performance.